2001
DOI: 10.1289/ehp.011091197
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of endocrine-disrupting chemicals in animals.

Abstract: A large number of chemical pollutants including phthalates, alkylphenolic compounds, polychlorinated biphenyls and polychlorinated dibenzodioxins, organochlorine pesticides, bisphenol A, and metals including lead, mercury, and cadmium have the ability to disrupt endocrine function in animals. Some of these same chemicals have been shown to alter cognitive function in animals and humans. Because hormonally mediated events play a central role in central nervous system development and function, a number of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(88 citation statements)
references
References 137 publications
(165 reference statements)
2
85
0
1
Order By: Relevance
“…The fattening of BFT in cages based on the capture of wild fish is an increasing practice in Mediterranean countries, practice, however, that should develop into a real BFT aquaculture, comprehensive of the entire life cycle. To this aim, beside the necessary technological improvements of farming facilities and protocols, there is a need of a modern molecular approach that seems promising for the studies of appropriate nutritional strategies, reproduction physiology and animal welfare, as well as lifestyle and response to endocrine disruptor pollutants (Schantz and Widholm, 2001). This approach will certainly benefit from the availability of EST databases.…”
Section: Discussionmentioning
confidence: 99%
“…The fattening of BFT in cages based on the capture of wild fish is an increasing practice in Mediterranean countries, practice, however, that should develop into a real BFT aquaculture, comprehensive of the entire life cycle. To this aim, beside the necessary technological improvements of farming facilities and protocols, there is a need of a modern molecular approach that seems promising for the studies of appropriate nutritional strategies, reproduction physiology and animal welfare, as well as lifestyle and response to endocrine disruptor pollutants (Schantz and Widholm, 2001). This approach will certainly benefit from the availability of EST databases.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic is said to act as an endocrine disruptor, upsetting the action of hormones by blocking or mimicking them (http://www/mindfully.org/Pesticide/Arsenic-DistruptsHormones.htm). Epidemiologic studies have revealed that long-term exposure to inorganic arsenic is associated with an increased risk of cancer of the lung, skin, liver, bladder, possibly kidney and colon, hyperkeratosis, diabetes and cardiovascular disease (Schantz and Widholm 2001). Consequently, the direct use of water from the receiving stream and the adjourning Opa river downstream could be detrimental to aquatic biota and humans.…”
Section: Resultsmentioning
confidence: 99%
“…Some chemical pollutants may act as hormone mimics and thus affect the central nervous system [1]. A number of environmental pollutants have been shown to disrupt endocrine function in animals, leading to long-lasting cognitive deficits in primates [2], and are likely to reprogramme (neuro)physiological set-points and to increase susceptibility to disease later in life [3].…”
Section: Methodsmentioning
confidence: 99%